Melting ternary hybrid nanofluid stagnation point flow with velocity slip past a stretching/shrinking sheet: Numerical simulation and validation via P2SATRA - Wahid, Nur Syahirah; Zamri, Nur Ezlin; Mohd Jamaludin, Siti Zulaikha; Norzawary, Nur Hazirah Adilla; Mohd Kasihmuddin, Mohd Shareduwan; Mansor, Mohd. Asyraf; Md Arifin, Norihan; Pop, Ioan (Elsevier, 2025)
Ternary hybrid nanofluids are crucial to be modeled and researched before their commercial application as a heat transfer fluid. This study investigates the stagnation point flow of a ternary hybrid nanofluid past a stretching/shrinking sheet, focusing on the influence of the melting parameter and second-order velocity slip. The governing partial differential equations (PDEs) are initially formulated and subsequently reduced to ordinary differential equations (ODEs). These ODEs are further transformed into first-order form and numerically solved using the bvp4c solver in MATLAB. Stability analysis is conducted due to the existence of two potential solutions, of which only one proves stable upon analysis. The numerical results indicate significant enhancements in heat transfer performance under conditions of elevated melting and enhanced velocity slip. Reducing the melting parameter and second-order velocity slip may expand the solution range, leading to a delay in boundary layer separation. The stable numerical solution for the heat transfer rate is then validated with the use of a logic mining model namely Permutation 2 Satisfiability Reverse Analysis (P2SATRA). The most accurate induced logic, chosen to illustrate the overall relationship between the selected parameters is achieved in the third fold of a 10-fold cross-validation, yielding an accuracy of 0.81818.